ANALISIS DETERMINAN EFEKTIVITAS AUDIT INTERNAL PADA SEKTOR PEMERINTAHAN - Budi Prakoso, Nawa; Ratmono, Dwi (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine factors which affect (determinants) internal audit effectiveness in the public sector. This study is a replication of the research that has been done by Alzeban and Gwiliam (2014)  in Saudi Arabia, with differences in location, object, sampling and analysis methods.The study was conducted at an internal auditor in eight inspectorate office districts / cities and provinces of Yogyakarta and Central Java. The total sample is 137 respondents. This study uses primary data in the form of a questionnaire. PLS analysis testing techniques are used to prove the research hypothesis.The result of this study shows that the competence of internal auditors, management support for internal audit and the independence of the internal audit proved a significant effect on the internal audit effectiveness. While the relationship between the internal auditor with the external auditor does not affect the internal audit effectiveness.